GRAPHIC ORGANIZER “BEHIND THE ARROW” AS AN ASSISTANT IN STUDYING GRAMMAR TOPICS IN RUSSIAN LANGUAGE LESSONS (Web of Teachers: Inderscience Research, 2024)
This article proposes the effective implementation of the author’s graphic organizer “Behind the Arrow” in the process of studying grammatical topics in Russian language lessons, the main goal of which is to develop students’ conscious mastery of complex concepts of Russian grammar. The “Behind the Arrow” organizer helps simplify the study of grammatical topics.